Influence of Filler Materials on Bituminous Mastic Rheology at High Temperatures - Sivaprakash G.; Padmarekha Ajithkumar (Civil Engineering Journal, 2024)
The mixing and compaction temperatures of the bituminous mixture are determined by the viscosity of the binder. It was always a concern to understand the influence of the type of filler on the workability of the bituminous mixture. The interaction of the filler with the bitumen plays a key role in this. The inert filler has a physical interaction with the binder, and the active filler will have both a physical and chemical interaction. Based on the type of interaction, the viscosity and shear thinning characteristics of the mastic (binder + filler) change, which will hence influence the workability of the bituminous mixture. An experimental investigation is conducted to measure the viscosity of the mastic with two types of filler, one chosen from the active filler category (hydrated lime) and another from the inert filler category (quarry dust). A shear rate sweep experiment was carried out within the temperature range of 100 to 160 °C to analyze the Newtonian and shear thinning responses of the mastic. Results indicate that, for an equivalent weight proportion of the filler, mastic containing quarry dust exhibited elevated Newtonian viscosity and zero-shear viscosity (as predicted using the Carreau Yasuda Model). Additionally, quarry dust mastic demonstrated a higher rate of shear thinning. Consequently, the beneficial effect of shear thinning during the compaction of bituminous mixtures has the potential to enhance workability and streamline the compaction process. Doi: 10.28991/CEJ-2024-010-02-013 Full Text: PDF